Neurofilament light chain serum levels correlate with 10‐year MRI outcomes in multiple sclerosis. Issue 12 (16th October 2018) - Chitnis, Tanuja; Gonzalez, Cindy; Healy, Brian C.; Saxena, Shrishti; Rosso, Mattia; Barro, Christian; Michalak, Zuzanna; Paul, Anu; Kivisakk, Pia; Diaz‐Cruz, Camilo; Sattarnezhad, Neda; Pierre, Isabelle V.; et al.
Abstract: Objective: To assess the value of annual serum neurofilament light (NfL) measures in predicting 10‐year clinical and MRI outcomes in multiple sclerosis (MS). Methods: We identified patients in our center'sC omprehensiveL ongitudinalI nvestigations inM S atB righam and Women's Hospital (CLIMB) study enrolled within 5 years of disease onset, and with annual blood samples up to 10 years ( n = 122). Serum NfL was measured using a single molecule array (SIMOA) assay. An automated pipeline quantified brain T2 hyperintense lesion volume (T2LV) and brain parenchymal fraction (BPF) from year 10 high‐resolution 3T MRI scans. Correlations between averaged annual NfL and 10‐year clinical/MRI outcomes were assessed using Spearman's correlation, univariate, and multivariate linear regression models. Results: Averaged annual NfL values were negatively associated with year 10 BPF, which included averaged year 1–5 NfL values (unadjusted P < 0.01; adjusted analysis P < 0.01), and averaged values through year 10. Linear regression analyses of averaged annual NfL values showed multiple associations with T2LV, specifically averaged year 1–5 NfL (unadjusted P < 0.01; adjusted analysis P < 0.01). Approximately 15–20% of the BPF variance and T2LV could be predicted from early averaged annual NfL levels. Also, averaged annual NfL levels with fatigue score worsening between years 1 and 10 showed statistically significant associations. However, averaged NfL measurements were not associated with year 10 EDSS, SDMT or T25FW in this cohort. Interpretation: Serum NfL measured during the first few years after the clinical onset of MS contributed to the prediction of 10‐year MRI brain lesion load and atrophy.